2016
DOI: 10.1002/art.39520
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Noncoding RNAs Mediate the Human Chondrocyte Inflammatory Response and Are Differentially Expressed in Osteoarthritis Cartilage

Abstract: ObjectiveTo identify long noncoding RNAs (lncRNAs), including long intergenic noncoding RNAs (lincRNAs), antisense RNAs, and pseudogenes, associated with the inflammatory response in human primary osteoarthritis (OA) chondrocytes and to explore their expression and function in OA.MethodsOA cartilage was obtained from patients with hip or knee OA following joint replacement surgery. Non‐OA cartilage was obtained from postmortem donors and patients with fracture of the neck of the femur. Primary OA chondrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 46 publications
13
94
0
Order By: Relevance
“…Meanwhile, other studies have revealed that long noncoding RNA UFC1 promotes proliferation of chondrocyte in osteoarthritis by acting as a sponge for miR-34a [29]. In the present study, we found that lncRNA-CIR upregulates in OA patients, which is consistent with previous studies [1]. Further functional study demonstrates that miR-27b inhibits lncRNA-CIR by directly targeting its 3’UTR.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Meanwhile, other studies have revealed that long noncoding RNA UFC1 promotes proliferation of chondrocyte in osteoarthritis by acting as a sponge for miR-34a [29]. In the present study, we found that lncRNA-CIR upregulates in OA patients, which is consistent with previous studies [1]. Further functional study demonstrates that miR-27b inhibits lncRNA-CIR by directly targeting its 3’UTR.…”
Section: Discussionsupporting
confidence: 82%
“…Based on the aforementioned data, we speculate that lncRNA-CIR plays pivotal role in OA. As a matter of fact, many reports have found that lncRNA-CIR is involved in ECM degradation [1, 30]. Thus, it is essential to fully understand the detailed mechanism of lncRNA-CIR in OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PACER is overexpressed in tissue samples from osteosarcoma when compared with control tissue and osteoblasts, and it enhances osteosarcoma cell proliferation and invasion (46). It is highly expressed in both knee and hip osteoarthritis chondrocytes when compared with non-osteoarthritic samples, suggesting a possible role in mediating inflammation-driven cartilage damage in osteoarthritis (54). Lethe is found to enhance the replication of the hepatitis C virus by suppressing interferon-stimulated gene expression after a type 1 interferon response (69).…”
Section: Lncrnas and Pathogenesis Of Inflammatory Diseasementioning
confidence: 99%
“…Mechanistically, THRIL acts as a scaffold through interacting with heterogeneous nuclear ribonucleoprotein L (hnRNPL), and this complex binds to the TNF-␣ promoter to induce its transcription. Up-regulated after stimulation with LPS, IL-1␤, or TNF-␣, PACER has been shown to regulate the expression of a neighboring gene, PTGS2 (COX-2), a key inflammatory gene (46,53,54). PACER functions as a decoy by binding and sequestering NF-B p50 homodimers, which lack transcription activation domains, away from the PTGS2 promoter.…”
Section: Lncrnas As Enhancers Of the Inflammatory Responsementioning
confidence: 99%